2017
DOI: 10.1002/cbin.10735
|View full text |Cite
|
Sign up to set email alerts
|

TNFR1 and TNFR2 differentially mediate TNF‐α‐induced inflammatory responses in rheumatoid arthritis fibroblast‐like synoviocytes

Abstract: TNF-α has long been implicated in the progression of rheumatoid arthritis (RA). However, how the receptors of TNF-α, namely TNFR1 and TNFR2, mediate TNF-α-induced inflammatory responses in fibroblast-like synoviocytes (FLS) in RA has not been elucidated. In the present study, primary FLS cells were isolated from RA patients and treated with TNF-α in vitro. The exogenous TNF-α induced the expression and release of endogenous TNF-α in FLS. In addition, TNF-α led to gradual downregulation of TNFR1 following 1 h t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Although RA-FLS contains both TNFR1 and TNFR2 (8), 'death signal' originated from TNFR1 is suppressed (38) and NF-κB signaling pathway is highly activated (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although RA-FLS contains both TNFR1 and TNFR2 (8), 'death signal' originated from TNFR1 is suppressed (38) and NF-κB signaling pathway is highly activated (7).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we also detected a dramatic increase in the proportion of TNFR2 + Tregs in TILs compared to PB, indicating a recruitment of TNFR2 + Tregs into the tumor microenvironment from the periphery, which possibly contributed to the tumor immune evasion. An elevated level of TNFR2 + Tregs is correlated with highly immunosuppressive microenvironment in malignant diseases, such as acute myeloid leukemia (AML) [ 19 ], lung cancer [ 20 ], and ovarian cancer [ 21 ], as well as in autoimmune disorders including type 1 diabetes and rheumatoid arthritis [ 22 , 23 ]. Ex vivo experiments also demonstrated a novel regulatory role of TNFR2 on Treg cell function and expansion [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exterior changes involve joint malformation, swelling, and joint dysfunction [ 3 , 4 ], while interior pathological changes mainly involve synovial hyperplasia and cartilage destruction. All of these changes are accompanied by systemic inflammatory responses [ 5 , 6 ], involving many cytokines, such as TNF- α [ 7 , 8 ] and IL-6 [ 9 11 ], which are responsible for initiating, propagating, and maintaining inflammation [ 12 ] in a complex network [ 13 ]. Recent studies have shown that TNF- α governs the crosstalk between fibroblast-like synoviocytes and chondrocytes [ 12 ] and might regulate the expressional changes in matrix-degrading enzymes and inflammatory mediators in fibroblast-like synoviocytes [ 12 ] and induce the inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%